Modelling the Energy Transition Cultures, Visions, Narratives - Erdbeer, Robert Matthias; Hagenmeyer, Veit; Stierstorfer, Klaus (Poetics of Modelling, 2025)
XXXI, 408 p. 51 illus., 42 illus. in color.